An aetiology‐based subanalysis of the Telerehabilitation in Heart Failure Patients (TELEREH‐HF) trial. (1st February 2021) - Szalewska, Dominika; Główczyńska, Renata; Piotrowicz, Ryszard; Kowalik, Ilona; Pencina, Michael J.; Opolski, Grzegorz; Zaręba, Wojciech; Banach, Maciej; Orzechowski, Piotr; Pluta, Sławomir; Irzmański, Robert; Kalarus, Zbigniew; et al.
Abstract: Aims: The aim of our study was to analyse the benefits of a 9 week hybrid comprehensive telerehabilitation (HCTR) programme in heart failure (HF) patients according to aetiology, as a subanalysis of the Telerehabilitation in Heart Failure Patients (TELEREH‐HF) trial. Methods and results: Overall, 555 (65.3%) patients with ischaemic (IS) and 295 (34.7%) patients with non‐ischaemic (NIS) HF aetiology were randomized. There were no differences between the effect of HCTR and usual care (UC) on the primary outcome of number of days alive and out of the hospital in 26 months from the time of randomization in either aetiology (Wilcoxon–Mann–Whitney test), and no heterogeneity of effect between the aetiologies was noted (van Elteren test, P = 0.746). In Cox proportional hazards regression analysis, treatment was not independently associated with the secondary outcomes. For all‐cause mortality, the adjusted hazard ratio for HCTR vs. UC was 0.90 (95% confidence interval, 0.54–1.51) in IS and 1.42 (95% confidence interval, 0.69–2.94) in NIS ( P interaction = 0.316). Differences between HCTR and UC in terms of change in the 6 min walk test distance and cardiopulmonary exercise test time after 9 weeks reached statistical significance in the IS arm ( P = 0.015 and P < 0.001, respectively), but not in the NIS arm; however, tests of heterogeneity indicated no statistically significant differences. Conclusions: The trial showed no difference between HCTR and UC in the primary outcome of percentage of days alive and out of the hospital for either IS or NIS aetiology. Moreover, the magnitude of changes in the clinical and functional statuses of the HF patients did not differ by aetiology. HCTR might have had beneficial effects on the 6 min walk test distance and cardiopulmonary exercise test time after 9 weeks in the IS patients; however, the effect was not statistically significantly different from that observed in the NIS patients.